2003
DOI: 10.1023/b:thro.0000024052.79415.62
|View full text |Cite
|
Sign up to set email alerts
|

4G/5G PAI-1 Promoter Polymorphism and Acute-Phase Levels of PAI-1 Following Coronary Bypass Surgery: A Prospective Study

Abstract: Postoperative PAI-1 concentrations of patients undergoing elective coronary bypass surgery are higher in carriers of the 4G-allele than in 5G/5G homozygotes as a result of higher baseline values. Knowledge of 4G/5G status may be useful to predict acute-phase PAI-1 concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
2
16
0
2
Order By: Relevance
“…However, the association between carriage of the PAI-1 5G allele and change in PAI-1 mRNA, with greater reduction in PAI-1 mRNA in carriers of the 5G allele, may be an equivalent finding. This is in concordance with previous studies demonstrating lower PAI-1 levels in patients homozygous for 5G (24,1).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, the association between carriage of the PAI-1 5G allele and change in PAI-1 mRNA, with greater reduction in PAI-1 mRNA in carriers of the 5G allele, may be an equivalent finding. This is in concordance with previous studies demonstrating lower PAI-1 levels in patients homozygous for 5G (24,1).…”
Section: Discussionsupporting
confidence: 83%
“…Patients carrying the 4G allele have a 20% higher basal level of PAI-1 than those carrying the 5G allele (24). Our methods of measuring change in mRNA without an absolute measurement of mRNA concentrations does not permit a comparison of absolute PAI-1 mRNA levels with previously published PAI-1 protein concentrations.…”
Section: Discussionmentioning
confidence: 78%
“…Since the PAI-1 4G variant has been shown to be associated with higher PAI-1 levels in plasm [12][13][14] and in tissue, [15][16][17] our data suggest that PAI-1 promotes neointima proliferation. This hypothesis for the role of PAI-1 is supported by a number of reports on a positive correlation between post-PTCA PAI-1 levels or activity and restenosis, 18-23 but contradicted by one study which could not find an association between the PAI-1 4G/5G polymorphism and restenosis.…”
Section: Discussionmentioning
confidence: 70%
“…The functionality of PAI-1 has been extensively investigated and the majority of results indicate that the 4G variant leads to higher expression levels. 12,13,[15][16][17] In contrast, little evidence is avail-able regarding APC levels in Factor V Leiden carriers and carriers of the PAI-1 4G/5G genotypes. P. Weiler et al observed only marginal augmentation of protein C activation in Factor V Leiden-mice.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…For example, PAI-1 levels in the blood are increased within 1 h of major surgery, severe trauma, and myocardial infarction (D'Angelo, Kluft et al 1985;Kluft, Verheijen et al 1985;Burzotta, Iacoviello et al 2003;. A major source of PAI-1 is liver because it is an acute phase protein ).…”
Section: Introductionmentioning
confidence: 99%